2022
DOI: 10.1038/s41598-022-06748-w
|View full text |Cite|
|
Sign up to set email alerts
|

ACC-BLA functional connectivity disruption in allergic inflammation is associated with anxiety

Abstract: Allergic asthma is a chronic inflammatory respiratory disease. Psychiatric disorders, including anxiety are associated with poorer treatment response and disease control in asthmatic patients. To date, there is no experimental evidence describing the role of peripheral inflammation on the oscillatory activities in the anterior cingulate cortex (ACC) and basolateral amygdala (BLA), two major brain structures modulating anxiety. In the present work we evaluated lung and brain inflammatory responses, anxiety-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…In addition, allergic inflammation leads to enhanced functional connectivity within the mPFC-amygdala circuit, while disrupting the dynamic interactions of the mPFC-amygdala circuit may promote anxiety-related behaviors with asthma [ 151 ]. Furthermore, a recent study from the same lab showed that allergic inflammation induced an increase in neuronal activity, and functional connectivity of the ACC-BLA circuit was correlated with the level of anxiety [ 152 ]. Inflammation-associated mood change reduced the connectivity of sACC to the amygdala, which was modulated by peripheral IL-6 [ 102 ].…”
Section: Amygdala Neuroinflammation and Psychiatric Disordersmentioning
confidence: 99%
“…In addition, allergic inflammation leads to enhanced functional connectivity within the mPFC-amygdala circuit, while disrupting the dynamic interactions of the mPFC-amygdala circuit may promote anxiety-related behaviors with asthma [ 151 ]. Furthermore, a recent study from the same lab showed that allergic inflammation induced an increase in neuronal activity, and functional connectivity of the ACC-BLA circuit was correlated with the level of anxiety [ 152 ]. Inflammation-associated mood change reduced the connectivity of sACC to the amygdala, which was modulated by peripheral IL-6 [ 102 ].…”
Section: Amygdala Neuroinflammation and Psychiatric Disordersmentioning
confidence: 99%
“…To further explore this issue, we computed theta coherence between these regions, which is a phase-based connectivity method and is reported to be a neural code of psychiatric phenomena 2 , 8 , 10 , 11 , 20 . OB-mPFC theta coherence was significantly higher in the EPM (maze = 0.41 ± 0.04, baseline = 0.24 ± 0.02, p = 0.006; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive performance requires coherent activity of distinct brain regions, often referred to as the Communication-Through-Coherence (CTC) hypothesis 25 , 26 . In this line, neural oscillations have fundamental implications in synchronizing the activity between different brain structures 2 , 8 , 11 , 14 , 15 , 20 . Preceding works establish associations between enhanced theta synchronization in several brain circuits and cognitive performance or psychiatric status 2 , 8 , 11 , 15 , 18 , 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, it found that in other allergic airway diseases, especially allergic asthma, there is not only bilateral communication in symptomatology but also bilateral connection in material/structural circuits. For instance, inflammatory mediators produced in the lungs when allergic asthma occurs, such as TH2‐type cytokines (IL‐4 and IL‐5), act on the fiber endings of sympathetic, parasympathetic, and sensory nerves, on the one hand, they can penetrate the blood–brain barrier leading to changes in the structure and function of related brain regions, such as activating microglia, altering the functional connectivity of the anterior cingulate cortex‐basolateral amygdala (ACC‐BLA) circuit by enhancing the oscillatory activity of related brain waves, and then inducing the production of anxiety behavior (Gholami‐Mahtaj et al, 2022). On the other hand, various neurotransmitters and neuropeptides released by nerve fibers promoted by immunoinflammatory activation in the brain regions, such as norepinephrine (NA), acetylcholine (Ach), and VIP, can directly affect immune cells, exacerbate the TH2 inflammatory response in asthma, lead to remodeling of lung structures, such as the release of Ach will induce the contraction of bronchial smooth muscle, and aggravate the pulmonary symptoms of asthma (Kabata & Artis, 2019; Nassenstein et al, 2018).…”
Section: Summary and Prospectmentioning
confidence: 99%